Targeted next‐generation sequencing in myelodysplastic syndromes and prognostic interaction between mutations and IPSS‐R. Issue 12 (20th October 2017) - Tefferi, Ayalew; Lasho, Terra L.; Patnaik, Mrinal M.; Saeed, Lyla; Mudireddy, Mythri; Idossa, Dame; Finke, Christy; Ketterling, Rhett P.; Pardanani, Animesh; Gangat, Naseema
Abstract: A 27‐gene panel was used for next‐generation sequencing (NGS) in 179 patients (median age 73 years) with primary myelodysplastic syndromes (MDS); risk distribution according to the revised International Prognostic Scoring System (IPSS‐R) was 11% very high, 18% high, 17% intermediate, 38% low and 16% very low. At least one mutation/variant was detected in 147 (82%) patients; 23% harbored three or more mutations/variants. The most frequent mutations/variants included ASXL1 (30%), TET2 (25%), SF3B1 (20%), U2AF1 (16%), SRSF2 (16%), TP53 (13%), RUNX1 (11%), and DNMT3A (10%). At a median follow up of 30 months, 148 (83%) deaths and 26 (15%) leukemic transformations were recorded. Multivariable analysis of mutations/variants identified ASXL1 (HR 1.7, 95% CI 1.2‐2.5), SETBP1 (HR 4.1, 95% CI 1.6‐10.2) and TP53 (HR 2.2, 95% CI 1.3‐3.4) as risk factors for overall and SRSF2 (HR 3.9, 95% CI 1.5‐10.2), IDH2 (HR 3.7, 95% CI 1.2‐11.4), and CSF3R (HR 6.0, 95% CI 1.6‐22.6) for leukemia‐free survival. Addition of age to the multivariable model did not affect these results while accounting for IPSS‐R weakened the significance of TP53 mutations/variants ( P = .1). An apparently favorable survival impact of SF3B1 mutations was no longer evident after adjustment for IPSS‐R. Approximately 41% and 20% of patients harbored at least one adverse mutation/variant for overall and leukemia‐free survival, respectively. Number of mutations/variants did not provide additional prognostic value. The survival impact of adverse mutations was most evident in IPSS‐R very low/low risk patients. These observations suggest that targeted NGS might assist in treatment decision‐making in lower risk MDS.